SUGGESTIVE ROLE OF EYE-STALK OF MACROBRACHIUM GANGETICUM BATE, 1868 IN REGULATION OF ITS REPRODUCTIVE BEHAVIOUR. - Gupta, Akhilesh Kumar (Journal of Indian Fisheries Association, 2009)
Role of eye-stalk of Macrobrachium gangeticum Bate, 1868 in its reproductive behaviour has been examined by conducting deletion and addition experiments. Eye-stalk ablation induced gonadal maturity in both sexes, leading to change in colour and size of ovaries and increase in GSI and oocyte diameter in females and increased length of testes and diameters of seminiferous tubules in males. Injection of eye-stalk extracts tended to at least partly restrict the effects in both sexes. The experiments thus suggested that the eye-stalk of M.gangeticum released some gonad inhibiting factors. Key words: Macrobrachium gangeticum, Eye-stalk, Gonads.